Sub-group Analyses from the EXTEND Study: a Randomised, Controlled, Open-Label, Phase III/IV Study Comparing the Efficacy of Extended-Pulsed Fidaxomicin with Standard Vancomycin Therapy for Sustained Clinical Cure of Clostridium difficile Infection in an Older Population. (4th October 2017) - Cornely, Oliver A; Vehreschild, Maria J G T; Adomakoh, Nicholas; Georgopali, Areti; Karas, Andreas; Kazeem, Gbenga; Guery, Benoit
Abstract: Background: In vitro gut model evidence suggests an extended-pulsed fidaxomicin, a narrow-spectrum macrocyclic antibiotic, regimen (EPFX) may be equivalent to standard vancomycin (SV) for resolving Clostridium difficile infection (CDI), but with a potentially greater capacity to prevent recurrence by facilitating gut microbiota recovery. EXTEND was the first multicentre study to compare clinical outcomes for EPFX and SV; this sub-group analysis investigated the impact of baseline factors. Methods: Patients aged ≥60 years with CDI were randomised (1:1) to receive either EPFX 200 mg tablets, twice-daily on Day 1–5 and once-daily on alternate days on Day 6–25; or SV 125 mg capsules, four-times daily on Day 1–10. The primary objective was sustained clinical cure (SCC) of CDI 30 days after end of treatment (EOT): Day 40 for SV and Day 55 for EPFX. Secondary efficacy endpoints included clinical response at Day 12 and at 2 days after EOT, and SCC at Day 40, 55 and 90. Patients who dropped out of the study after starting treatment were considered failures for SCC. Patients were stratified by baseline CDI severity, presence of cancer, and number of CDI episodes in the 3 months before the study. Primary and secondary endpoints were analyzed in these sub-groups. Deaths were also recorded and safety evaluated. Results: Efficacy was assessed in 356 patients; 58.1% were female, median (range) age 75 (60–95) years. At baseline, 36.5% had severe CDI; 15.4% and 5.6% had one and two prior CDI episodes, respectively. The primary endpoint, SCC at 30 days after EOT, was higher for EPFX than SV in all subgroups (Figures 1–3), but did not reach statistical significance. For the secondary endpoints, differences in clinical response were not statistically significant; differences in SCC with EPFX vs. SV were significant (p value <0.05) for non-severe CDI, no cancer and no prior CDI episode on Day 40, 55 and 90. Incidence of deaths did not differ between the treatment groups: 29/183 (15.8%) EPFX and 36/181 (19.9%) SV patients; P = 0.54. Safety was similar with both treatments. Conclusion: There was a consistent trend for higher absolute SCC in the EPFX group than the SV group across all sub-groups and time points, which reached statistical significance from Day 40 onwards in some sub-groups. Disclosures: O. A. Cornely, Astellas Pharma, Inc.: Consultant, Research Contractor and Speaker's Bureau, Consulting fee, Research grant and Speaker honorarium; M. J. G. T. Vehreschild, Astellas Pharma, Inc.: Investigator, Consulting fee and Research support; N. Adomakoh, Astellas Pharma, Inc.: Employee, Salary; A. Georgopali, Astellas Pharma, Inc.: Employee, Salary; A. Karas, Astellas Pharma, Inc.: Employee and Patent WO2015169451 A1 pending, Salary; G. Kazeem, Astellas Pharma, Inc.: Consultant, Salary; B. Guery, Astellas Pharma, Inc.: Investigator, Consulting fee and Research support